Dinâmica da distribuição diamétrica de povoamentos de Pinus taeda L. em diferentes idades e espaçamentos - Netto, Camila Carelli (2008)
The diameter distribution through of mathematical formulations can be a factor of importance to the planning and control of forest activities, determining the production and growth of the trees, allowing the knowledge of future productions of stand. The objective of this study is determine the distribution of frequencies per diameter class and a prognosis model of density probability in a stand of Pinus taeda L. without thinning, in different ages and spacing. To the determination if the diameter distribution were used the probabilities distributions Normal, Weibull, Ln-normal and Gamma, through of procedure CAPABILITY (Proc Capability) of statistical program SAS. To determine the prognosis of probability of frequencies per diameter class were applied the method proposed by Cao (2004), through of Weibull distribution with two parameters, processed and adjusted using the statistical program SAS. The experimental design used was randomized blocks, with nine treatments, each treatment consists of three repetitions. The analyses were made only to the treatments with spacing 2 x 2 m 2 x 3 m, on the ages of 6, 8, 10, 12, 14, 16 and 18 years old. The results indicated that the Normal distribution have the best adjustment on the ages of 6, 8 and 10 years for both spacing 2 x 2 m and for the 2 x 3 m. In the age of 12, 14, 16 and 18 years the Ln-normal distribution is that best represents the distribution per diameter class in spacing 2 x 2 m, and the Gamma distribution for the spacing 2 x 3 m. The study of prognosis of frequency distribution by diameter class is represented effectively by Weibull distribution, adjusted by the method of Cao (2004), for spacing 2 x 2 m 2 x 3, at all ages evaluated.